Mothers' education and ANC visit improved exclusive breastfeeding in Dabat Health and Demographic Surveillance System Site, northwest Ethiopia - Tariku, Amare (PLoS One, 2017)
INTRODUCTION: Despite its proven benefit in reducing child mortality and morbidity, the coverage of exclusive breastfeeding (EBF) remains sub-optimal. In Ethiopia, about 52% of infants under six months of age were exclusively breastfed, implying the need for further identification of the barriers to optimal EBF practice. Therefore, this study aimed to investigate EBF and its determinants in the predominantly rural northwest Ethiopia. METHODS: The study was conducted at the Dabat Health and Demographic Surveillance System (HDSS) site, which is located in Dabat District, northwest Ethiopia. A total of 5,227 mothers with children under five years of age were included for analysis. Multivariable binary logistic regression analysis was employed to identify factors associated with EBF. The Adjusted Odds Ratio (AOR) with a 95% Confidence Interval (CI) was estimated to show the strength of association. A P-value of <0.05 was used to declare statistical significance. RESULTS: About 54.5% [95% CI: 51.9, 57.1] of the mothers practiced EBF. Mothers' education [AOR = 2.10; 95% CI: 1.63, 2.71], age (20–35 years) [AOR = 1.39; CI: 1.07, 1.80], urban residence [AOR = 1.28; 95% CI: 1.07, 1.54], at least one ANC visit [AOR = 1.41; 95% CI: 1.23,1.61], initiation of breastfeeding within one hour of birth [AOR = 1.32; 95% CI: 1.15,1.50], richer household [AOR = 1.34; 95% CI: 1.07, 1.65], and withholding prelacteal feeds [AOR = 1.34; 95% CI: 1.17, 1.53] were found important determinants of EBF. CONCLUSION: In this study area, the prevalence of EBF is lower than the national as well as the global recommendation for universal coverage of EBF. Therefore, strengthening the implementation of Infant and Young Child Feeding strategy (IYCF) and maternal health care utilization are essential for stepping up EBF coverage. Moreover, attention should be given to uneducated, rural resident, and adolescent mothers.